2014
DOI: 10.4085/1062-6050-49.3.51
|View full text |Cite
|
Sign up to set email alerts
|

Injury Characteristics in the German Professional Male Soccer Leagues After a Shortened Winter Break

Abstract: Context: The winter break in the top 2 German professional soccer leagues was shortened from 6.5 to 3.5 weeks in the 2009–2010 season. Objective: To investigate whether this change affected injury characteristics by comparing the second half of the 2008–2009 (long winter break) with the equivalent period in the 2009–2010 season (short winter break). Design: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 26 publications
1
35
0
2
Order By: Relevance
“…To the best of our knowledge, only one study has evaluated the effect of a winter break on injury rates. 1 Shortening of the winter break from 6.5 to 3.5 weeks was not associated with a change in the overall injury risk in two top male football leagues in Germany across the 2008/2009 and 2009/2010 seasons, but it was associated with a higher number of training and knee injuries. 1 Team schedules vary in the different football playing countries.…”
Section: Introductionmentioning
confidence: 81%
“…To the best of our knowledge, only one study has evaluated the effect of a winter break on injury rates. 1 Shortening of the winter break from 6.5 to 3.5 weeks was not associated with a change in the overall injury risk in two top male football leagues in Germany across the 2008/2009 and 2009/2010 seasons, but it was associated with a higher number of training and knee injuries. 1 Team schedules vary in the different football playing countries.…”
Section: Introductionmentioning
confidence: 81%
“…This means that, regardless of match running, players are able to maintain a level of technical activity through the entire season [40]. Dupont, et al [41] and aus der Funten, et al [42] found that, among top-level players, rest time between 72 and 96 h after a game was sufficient to ensure full regeneration of the body and a return to the optimal level of physical activity in players. Bloomfield, et al [43] and Konarski [44] both stated that training confers on players an ability to respond quickly and properly to increasing fatigue levels, allowing them to achieve an optimal level of recovery in advance of the season’s next game.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing prevention strategies for a given population requires understanding and obtaining evidence on the specific pattern of said sample. As such, several epidemiological investigations have been conducted worldwide, and is common practice in the main leagues, world tournaments 2 , 8 and World Cups. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%